The Role of Family Interpersonal Communication in Preserving Local Languages - Fadhliyah Rahma Muin; Wahyuni Husain; Siti Hardiyanti S (Institut Agama Islam Negeri Palopo, 2023)
This study discusses the Role of Family Interpersonal Communication in Preserving Regional Languages, especially Flores Families in Tabarano Village, Wasuponda District, East Luwu Regency. Flores in the Flores family in Tabarano Village, and the role of interpersonal communication of the Flores family in the preservation of the Flores language.Â This type of research is qualitative research.In order to obtain data in this study, the authors used techniques including observation, interviews, and documentation. The results of this study show an overview of the interpersonal communication of Flores families in Tabarano Village.Â Currently, the use of language when communicating tends to use Indonesian. day to day. And there are also family members whose children can speak Flores because they have been accustomed to using the Flores language since they were young and some of their children have attended school in Flores. The form of an illustration of preservation is by listening to the Flores language when speaking, teaching directly, and teaching the Flores language when their children question the meaning of the Flores language they hear. Family interpersonal communication is currently experiencing a shift such as the loss of the use of the Flores language when communicating with the family, then the use of the Flores language from the parents is answered with Indonesian by the child, then the use of the Flores language is mixed with Indonesian when speaking which makes the Flores language not superior in the preservation process. The lack of a positive response from children towards parents' efforts to preserve the Flores language so that parents also understand and adjust to what is in their environment.